Сellular composition and cytokine profile of synovial fluid in rheumatoid arthritis - E. V. Zhdanova; E. G. Kostolomova; D. E. Volkova; A. V. Zykov (Медицинская иммунология, 2022)
Rheumatoid arthritis (RA) ranks first among chronic joint diseases. The disease often affects people at their working age, being accompanied by significant decrease in the life quality of patients and their early disability. Rheumatoid arthritis is an immunoinflammatory rheumatic disease. Therefore, the immune system provides evolving focus of primary damage, its persistence and periodic exacerbation. Elucidation of intercellular relationships mediated by cytokines at various stages of the chronic inflammatory process is required in order to develop immunotherapeutic approaches, aimed for both recovery from exacerbations and maintenance of remission state. Purpose of our study was to evaluate cellular composition and cytokine profile of synovial fluid in the patients with rheumatoid arthritis at acute phase and in remission state.We have studied the samples of synovial fluid taken in 60 patients with rheumatoid arthritis, with 30 subjects being at acute stage of the disease, and 30 patients in remission. Cellular composition and cytokine profile were assessed in the clinical samples. There were 21 women and 9 men at the acute stage (57.0±15.4 years old), with the disease duration of 8.55±6.9 years. The average age of 19 women and 11 men examined in remission state was 53.5±10.9 years, with comparable duration of illness (6.9±5.8 years). The leukocyte phenotyping was performed with a CytoFLEX flow cytometer (Beckman Coulter, USA). The cytokine contents were measured by enzyme immunoassay using a standard set of reagents from the “Proteinovy Contour” LLC (Russia). The results were registered by a Multiscan photometer (Labsystems, Finland).During the disease exacerbation, the leukocyte contents in synovial fluid increased 2.4-fold, as compared to the remission values. The cellular infiltrate was represented by neutrophils, whereas the contents of lymphocytes and monocytes did not change. Increased migration of neutrophils was accompanied by an 8-fold increase in TNFα levels, compared with remission state, and IL-1β levels were increased by 6.3 times. The absolute number of CD3+T lymphocytes, CD16+CD56+B cells, and CD3-CD19+NK during exacerbation was similar to the remission levels. However, the number of T cell subpopulations was changed, i.e., the number of CD4+ lymphocytes was decreased, and CD8+ cell counts were increased, like as numbers of Treg lymphocytes and NKT cells which showed a significant increase. A 4.3-fold increase in the IL-4 concentration during the RA exacerbation suggested the predominance of Th2 immune response. During remission, the concentrations of IL-6 and IFNγ in synovial fluid were increased, respectively, by 1.5 times and by 2.5 times, which is typical for activated Th1 response.